2021
DOI: 10.1002/cam4.4506
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of NRF2 inhibition in melanoma reveals CD44 up‐regulation and increased apoptosis resistance upon vemurafenib treatment

Abstract: Malignant melanoma is the deadliest form of skin cancer and NRF2 has been proposed as a main regulator of tumor cell malignancy. Still the mechanisms how NRF2 is contributing to melanoma progression are incompletely understood. Here we analyzed the effects of either NRF2 induction or depletion, and we also quantified changes on the whole cell proteome level. Our results showed that inhibition of NRF2 leads to a loss of reactive oxygen species protection, but at the same time to an induction of an epithelial me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…The role of Nrf2 in EMT has raised researchers’ interest in the past years but studies demonstrate contradictory results. Some studies have demonstrated that Nrf2 activation is associated with EMT induction [ 21 , 45 , 46 ] while others, as our results suggest, demonstrate that Nrf2 impairment leads to the induction of the EMT program [ 47 , 48 , 49 ] or, in the same way, that Nrf2 activation is associated with EMT inhibition [ 50 , 51 , 52 ]. Interestingly, it has also been described that Nrf2 may act as a phenotypic stability factor in restricting complete EMT by maintaining the cells in a hybrid epithelial/mesenchymal state [ 23 , 53 ].…”
Section: Discussionsupporting
confidence: 68%
“…The role of Nrf2 in EMT has raised researchers’ interest in the past years but studies demonstrate contradictory results. Some studies have demonstrated that Nrf2 activation is associated with EMT induction [ 21 , 45 , 46 ] while others, as our results suggest, demonstrate that Nrf2 impairment leads to the induction of the EMT program [ 47 , 48 , 49 ] or, in the same way, that Nrf2 activation is associated with EMT inhibition [ 50 , 51 , 52 ]. Interestingly, it has also been described that Nrf2 may act as a phenotypic stability factor in restricting complete EMT by maintaining the cells in a hybrid epithelial/mesenchymal state [ 23 , 53 ].…”
Section: Discussionsupporting
confidence: 68%
“…Weitzenböck et al found that Nrf2 suppression leads to the expression of CD44 and the development of epithelial-mesenchymal transition phenotype. Of note, treatment of Nrf2 depleted cells with BRAF or MYC inhibitor results in a higher survival rate of melanoma cells [ 50 ]. This shows that antioxidant intervention could be a game-changing strategy for improving melanoma patient survival.…”
Section: Resultsmentioning
confidence: 99%
“… Nrf2 silencing increases melanoma cell viability, invasiveness, and the risk of metastasis. [ 50 ] Wang et al, 2022 The A375, and A2058 cell lines Following treatment with erastin and RSL3, the level of CAMKK2 mRNA was significantly elevated. Phosphorylation of CAMKK2 reduces during ferroptosis.…”
Section: Methodsmentioning
confidence: 99%
“…In preclinical experiments, vemurafenib increases cell death [30], [31], decreases proliferation [32], [33] and also affects cell migration [34]- [36]. Furthermore, exposure to vemurafenib can also modify the released EVs' content [37], [38].…”
Section: Introductionmentioning
confidence: 99%